Cyclic viscoplasticity testing and modeling of a service-aged P91 steel - Hyde, Christopher J.; Sun, Wei; Hyde, T.H.; Rouse, J.P.; Farragher, T.; O'Dowd, Noel P.; Leen, S.B. (American Society of Mechanical Engineers, 2014)
A service-aged P91 steel was used to perform an experimental program of cyclic mechanical testing in the temperature range of 400 °C–600 °C, under isothermal conditions, using both saw-tooth and dwell (inclusion of a constant strain dwell period at the maximum (tensile) strain within the cycle) waveforms. The results of this testing were used to identify the material constants for a modified Chaboche, unified viscoplasticity model, which can deal with rate-dependant cyclic effects, such as combined isotropic and kinematic hardening, and time-dependent effects, such as creep, associated with viscoplasticity. The model has been modified in order that the two-stage (nonlinear primary and linear secondary) softening which occurs within the cyclic response of the service-aged P91 material is accounted for and accurately predicted. The characterization of the cyclic viscoplasticity behavior of the service-aged P91 material at 500 °C is presented and compared to experimental stress–strain loops, cyclic softening and creep relaxation, obtained from the cyclic isothermal tests.